Perspektif Minat Melamar Calon Karyawan Dengan Employer Branding - Setyawan, Arel Saputra; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Companies compete to win customers and achieve competitive advantage. In addition, they also compete to win prospective employees who are competent in their fields. The recruitment process is an important step for companies in attracting prospective employees. Employer branding and corporate reputation are strategies used to introduce organizational values and form a positive image of the company in the community so that it can attract job applicants to join the company. This study uses a descriptive research type with a qualitative research method approach. The results of the study show that the implementation of employer branding and corporate reputation strategies has succeeded in attracting job applicants to join the company.